Unlawful Land Certificate Acquisition and its Implications for Legal Certainty of Land Rights in Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
The illegal acquisition of land certificates is a serious problem in Indonesia's land law system because it has the potential to eliminate legal certainty regarding land rights. Certificates that are supposed to serve as strong proof of rights can still be obtained thru unauthorized possession, manipulation of legal data, or deviations from administrative procedures. This research aims to analyze the acquisition of illegal land certificates from a land law perspective and its legal implications for legal certainty. The research method used is normative legal research with a statutory approach and a conceptual approach, examining Law Number 5 of 1960, Government Regulation Number 24 of 1997, and Government Regulation Number 18 of 2021. The research results indicate that land certificates obtained illegally contain legal defects and can be revoked, and also have administrative, civil, and criminal legal implications that directly disrupt legal certainty regarding land rights. Therefore, consistent law enforcement and strengthening the land registration system are needed to ensure legal protection and certainty of land rights in Indonesia.